فعالية إستراتيجية التفكير البصري في تصميم الملصق الإعلانى - الدريدى، إبتهاج حافظ Aldredy, Ebtehaj Hafez (الجمعية العربية للحضارة والفنون الإسلامية, 2018)
The tendency to use visual thinking operations comes as a bid to understand the world through contemplating images, a step to get different shapes of advertising designs outside typical style with a view to coming up with new designing horizons based on imagination, symbolism and creativity, thus, stimulating the recipient mind to try to deal with this symbolic side of the image and decrypt its codes and significance to deduct such invisible meaning lying in the advertising idea as well as to convert such meaning to a mental image. Visual thinking is an attempt to open up horizons to human imagination for free exploration outside the typical style of the advertising poster design
إن الإتجاه إلى استخدام عمليات التفكير البصري هو محاولة لفهم العام من خلال التبصر بالصور والتي تعتبر خطوة للخروج بتصميم الملصق الإعلاني على إختلاف أشكاله من الحيز النمطي إلى آفاق تصميمه جديدة قائمة على الخيال والرمزية والإبداع، مما يدفع العقل البشري للمتلقي لمحاولة التعامل مع الصورة الرموزية ودلالاتها وفك شفراتها لإستخلاص المعنى اللامرئي الكامن للفكرة الإعلانية في الملصق الإعلاني وتحويله إلى صورة عقلية، فالتفكير البصري هو محاولة لفتح الآفاق أمام الخيال الإنساني كي يتجول بحرية وانطلاق خارج النطاق النمطي لتميم الملصق الإعلاني.
Keywords: الإعلان الصادم; التفكير البصري; تصميم الملصق الإعلانى